Modeling the flexural evolution of the Amiran and Mesopotamian foreland basins of NW Zagros (Iran‐Iraq). Issue 3 (11th March 2015) - Saura, Eduard; Garcia‐Castellanos, Daniel; Casciello, Emilio; Parravano, Vanessa; Urruela, Aritz; Vergés, Jaume
Abstract The evolution of the Amiran and Mesopotamian flexural basins of the Zagros belt is approached by coupled 2‐D forward modeling of orogenic wedge formation, lithospheric flexural isostasy, and stream power erosion/transport/sedimentation. Thrust geometries and sequence of emplacement derived from geometric and kinematic models presented here are the inputs to our evolutionary model, constrained by basin geometry, sediment volume, and topography. Modeling results confirm that the Zagros flexural basins evolution is consistent with two stages of deformation: (1) the obduction stage involving the Kermanshah accretionary complex and a basement unit and (2) the collision stage, emplacing the Gaveh Rud and Sanandaj‐Sirjan domains in the hinterland and forming a basement duplex in the outer part. Results provide quantitative insights into processes involved in mountain and basin building. The lithospheric equivalent elastic thickness (Te) changed from 20 km during the Amiran stage (~90–50 Ma) to 55 km during the Mesopotamian subsidence stage (last 20 Myr). The Amiran basin results from flexure of the Arabian plate below the load of the Kermanshah cover and basement thrust sheets. During this stage, material eroded in the inner parts was enough to fill the flexural trough. The Mesopotamian basin formed in front of the outermost basement units flexing the Arabian plate. During this latter stage, material eroded from the orogenic wedge was not enough to fill the Mesopotamian basin. An additional longitudinal sediment supply of up to 200 m/Myr is required to fill the flexural basin.